2019
DOI: 10.31616/asj.2018.0237
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants in Spine Surgery: A Systematic Review to Determine Benefits and Risks

Abstract: Antidepressant drugs can be advantageous in treating psychiatric and non-psychiatric illnesses, including spinal disorders. However, spine surgeons remain unfamiliar with the advantages and disadvantages of the use of antidepressant drugs as a part of the medical management of diseases of the spine. Our review article describes a systematic method using the PubMed/Medline database with a specific set of keywords to identify such benefits and drawbacks based on 17 original relevant articles published between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…As described above, depression is associated with decreased physical activity and increased risk of developing dementia [ 139 , 140 ]. Anti-depressant drugs can be advantageous in treating SCI-mediated depression, including improving mood status and quality of life following surgery, and reducing risk of delirium and suicide [ 141 ]. Venlafaxine may be more appropriate for patients with SCI presenting with depression and/or nociceptive pain [ 142 , 143 , 144 ].…”
Section: Potential Therapeutic Interventionmentioning
confidence: 99%
“…As described above, depression is associated with decreased physical activity and increased risk of developing dementia [ 139 , 140 ]. Anti-depressant drugs can be advantageous in treating SCI-mediated depression, including improving mood status and quality of life following surgery, and reducing risk of delirium and suicide [ 141 ]. Venlafaxine may be more appropriate for patients with SCI presenting with depression and/or nociceptive pain [ 142 , 143 , 144 ].…”
Section: Potential Therapeutic Interventionmentioning
confidence: 99%
“…49 In a recent realworld, cohort study of five million surgical patients over a ten-year period, concomitant use of gabapentinoids with opioids was associated with an increased risk of opioid overdose and other opioid-related adverse events; however, the absolute risk of adverse events was low (number needed to treat for additional overdose to occur was more than 16,000 patients). 50 Other non-opioid medications with less established evidence base for post-operative pain management following spine surgery include antispasmodics, antidepressants, [51][52][53] melatonin, 54 vitamin C, 55 and cannabinoids. 56…”
mentioning
confidence: 99%
“…We have not used any drug therapy for combating depressive features during the treatment, even in the postoperative period. There is no consensus in the literature regarding the use of antidepressant drug in the spinal surgery patient and few risk factors as decreased platelet aggregation, chances of bleeding and poor bony fusion has been reported in the previous articles but more extensive randomized control trial are needed to prove the benefits and risk factors [25,26]. Many studies have shown that about 20-40% of the LCS patients have clinically significant depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%